PSIII-A-12 Longissimus Thoracis Mitochondrial Capacities and Temperament of Stocker Calves are Related to Meat Quality at Harvest in Brahman but not in Angus Cattle. (21st September 2022) - Semanchik, Pier L; Wesolowski, Lauren T; Simons, Jessica L; Guy, Chloey; Earnhardt, Audrey L; Perry, George A; Long, Charles R; Riley, David; Law, Dustin; Neuendorff, Don A; Machado, Tanner; Randel, Ron D; et al.
Abstract: Brahman cattle reportedly have decreased meat quality compared to Angus but little is known about the cellular mechanisms driving this difference. We hypothesized that live animal skeletal muscle mitochondria would be related to meat quality. Trapezius and longissimus thoracis (LT) samples were collected from 10-mo-old Angus and Brahman steers designated as calm, intermediate, or temperamental (n=12/group/breed) based on pen score and exit velocity at weaning. Samples were analyzed for citrate synthase (CS) and cytochrome c oxidase (CCO) activities as markers of mitochondrial volume density and function. Calm and temperamental LT samples were also analyzed for oxidative phosphorylation (P) and electron transfer (E) capacities via high-resolution respirometry. At approximately 14.5-mo-old, steers were placed in pens and fed ad libitum. After at least 120 d on feed, animals were harvested and 13 th rib LT samples were collected, vacuum packaged, aged 14d, frozen, then subjected to Warner-Bratzler Shear Force (WBSF). Impacts of temperament and breed on WBSF were determined using mixed linear models with breed, temperament, and breed × temperament as fixed effects. Relationships between mitochondrial variables and WBSF were determined using Pearson's Correlations. Regardless of temperament, WBSF was greater in Brahman than Angus steers (P< 0.0001). Temperament did not impact WBSF in Angus but temperamental Brahman had greater WBSF than both calm and intermediate Brahman (P≤0.01). CS and CCO activities at 10 mo of age were not correlated with WBSF. However, Brahman LT intrinsic (relative to CS) P with complex I (PCI ), maximal P with complexes I and II (PCI+II ), maximal E with complexes I and II (ECI+II ), and E with complex II only (ECII ) were positively correlated with WBSF (P≤0.05) while no LT mitochondrial capacity measures correlated with WBSF in Angus. These data may shed light on differences in skeletal muscle energetics leading to decreased meat quality in temperamental Brahman steers.